Design, Synthesis, and Analysis of Minor Groove Binder Pyrrolepolyamide-<svg style="vertical-align:-0.0pt;width:16.612499px;" id="M1" height="23.3125" version="1.1" viewBox="0 0 16.612499 23.3125" width="16.612499" xmlns:xlink="http://www.w3.org/1999/xlink" xmlns="http://www.w3.org/2000/svg"> <g transform="matrix(.022,-0,0,-.022,.062,23.25)"><path id="x1D7D0" d="M453 211h25l-46 -211h-415v23q97 102 151 166q42 49 81 110q51 78 51 148q0 56 -31.5 91.5t-87.5 35.5q-77 0 -122 -90h-28q67 204 223 204q82 0 132 -49.5t50 -133.5q0 -110 -114 -218l-162 -154h140q82 0 107 13q27 13 46 65z" /></g> <g transform="matrix(.016,-0,0,-.016,11.275,12.488)"><path id="x2032" d="M227 744l-123 -338l-31 15l73 368q12 3 41.5 -8t36.5 -20z" /></g> -Deoxyguanosine Hybrids - Kawashima, Etsuko; Ohba, Yusuke; Terui, Yusuke; Kamaike, Kazuo (Journal of Nucleic Acids, 2010)
Pyrrolepolyamide-2′-deoxyguanosine hybrids (Hybrid 2 and Hybrid 3) incorporating the 3-aminopropionyl or 3-aminopropyl linker were designed and synthesized on the basis of previously reported results of a pyrrolepolyamide-adenosine hybrid (Hybrid 1). Evaluation of the DNA binding sequence selectivity of pyrrolepolyamide-2′-deoxyguanosine hybrids was performed by CD spectral and Tm analyses. It was shown that Hybrid 3 possessed greater binding specificity than distamycin A, Hybrid 1 and Hybrid 2.